2016
DOI: 10.1111/pbi.12641
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a fusarium head blight resistance gene TaACT in wheat QTL‐2DL

Abstract: SummaryFusarium head blight (FHB) resistance in wheat is considered to be polygenic in nature. Cell wall fortification is one of the best resistance mechanisms in wheat against Fusarium graminearum which causes FHB. Metabolomics approach in our study led to the identification of a wide array of resistance‐related (RR) metabolites, among which hydroxycinnamic acid amides (HCAAs), such as coumaroylagmatine and coumaroylputrescine, were the highest fold change RR metabolites in the rachis of a resistant near‐isog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 57 publications
1
48
0
Order By: Relevance
“…In conclusion, the recent cloning of Fhb1 and 2DL (Kage et al ., ; Rawat et al ., ) from wheat has shown that much can be learned about the processes involved in host resistance through the cloning of genes providing quantitative FHB resistance.…”
Section: What Makes a Host Resistant To F Graminearum: Comparative Tmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, the recent cloning of Fhb1 and 2DL (Kage et al ., ; Rawat et al ., ) from wheat has shown that much can be learned about the processes involved in host resistance through the cloning of genes providing quantitative FHB resistance.…”
Section: What Makes a Host Resistant To F Graminearum: Comparative Tmentioning
confidence: 99%
“…For instance, metabolomics studies conducted on NILs with and without the 2DL QTL showed that hydroxycinnamic acid amides (HCAs), such as coumaroylagmatine, associated with resistance, were differentially produced between the resistant and susceptible NILs. Subsequent genetic mapping, followed by functional analyses using VIGS and the complementation of the Arabidopsis act mutant, identified the TaACT gene encoding an agmatine coumaroyltransferase as the gene underlying the 2DL QTL (Kage et al, 2017), demonstrating the usefulness of undertaking combinatorial approaches (Fig. 2).…”
Section: Combining Transcriptomics With Proteomics and Metabolomicsmentioning
confidence: 99%
“…Virus-induced gene silencing (VIGS) is a useful strategy for the study of gene function in cereals. It uses a Barley stripe mosaic virus (BSMV)-based silencing system in monocot plants (Bennypaul et al, 2012;Holzberg et al, 2002), and has been successfully utilized in wheat gene function studies (Ahmed et al, 2017;Kage et al, 2017;Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…All the phenolic acid and flavonoid compounds mentioned above exhibit strong antioxidant properties (Rice‐Evans et al ., ), which has been hypothesized to be the source of the strong down‐regulatory effect of ferulic acid and other phenolic compounds on Tri gene expression (Boutigny et al ., , ). Finally, it is notable that phenolic compounds have been found at high concentration in the silk of various resistant maize varieties (Reid et al ., ), wheat (Hamzehzarghani, ; Kumaraswamy et al ., ; Kage et al ., ) and barley (Bollina et al ., ; Kumaraswamy et al ., ).…”
Section: Targets In the Tri Gene Clusters Of Don And Nivalenol‐producmentioning
confidence: 99%